2018
DOI: 10.1158/1535-7163.mct-17-0887
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Depletion by TASIN-1 Induces Apoptotic Cell Death through the ER Stress/ROS/JNK Signaling in Colon Cancer Cells

Abstract: Truncated APC selective inhibitor-1 (TASIN-1) is a recently identified small molecule that selectively kills colorectal cancer cells that express truncated adenomatous polyposis coli (APC) by reducing cellular cholesterol levels. However, the downstream mechanism responsible for its cytotoxicity is not well understood. In this study, we show that TASIN-1 leads to apoptotic cell death via inducing ER stress-dependent JNK activation in human truncated APC colon cancer cells, accompanied by production of reactive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Endoplasmic reticulum (ER) stress is emerging as a modulator of different pathologies and as an important mechanism contributing to cancer cell death in response to therapeutic agents [15, 16]. In several instances, oxidative stress and the onset of ER stress occur together [17, 18]. Therefore, we examined the expression of ER stress-related proteins, such as p-eIF2α and ATF4 in IATL-treated prostate cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress is emerging as a modulator of different pathologies and as an important mechanism contributing to cancer cell death in response to therapeutic agents [15, 16]. In several instances, oxidative stress and the onset of ER stress occur together [17, 18]. Therefore, we examined the expression of ER stress-related proteins, such as p-eIF2α and ATF4 in IATL-treated prostate cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular cholesterol demands are increased in tumorigenesis to support membrane synthesis, cell proliferation, and survival (Bovenga et al, 2015). Conversely, lipid depletion is associated with reduced cell viability, metastasis, and tumor burden in cell and animal models (Sharma et al, 2019; Su et al, 2012; Zhang et al, 2018), whereas lipid‐lowering therapies have shown promise in decreasing risk and improving prognosis of numerous cancer types in human populations (Bovenga et al, 2015; Couttenier et al, 2017; Mondul et al, 2018). Thus, it is essential to elucidate the complex mechanisms underlying the relationship between cancer and cellular cholesterol metabolism in order to optimize prognostic and therapeutic practices (Chimento et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The IHC results indicated that JNK was transcribed and expressed after 540 mg/kg ZnO NPs exposure. These two genes had been reported to induce apoptosis [29]. Meanwhile, the genes which exhibited an increase could be indicative of the ZnO NPs induction of placenta ER stress.…”
Section: Discussionmentioning
confidence: 93%